Nilai Pendidikan Dalam Fawatih As-Suwar - amin efendi (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Metro, 2014)
The Qur'an is the holy book revealed by Allah. to the Prophet Muhammad. gradually through the Angel Gabriel to be delivered to mankind. This book contains the demands of life for mankind to survive life in this world and the hereafter, and the scripture which maintained its authenticity. One form of authenticity and purity of the Qur'an is the word form letter opener in the Qur'an which is known as as-suwar fawatih. There are ten kinds of fawatih as- suwar, namely: opening with praise to God (al-istiftah bi al itsana), opening with letters cut (Al-Ahruful Muqoto'ah), the opening of the call (al-istiftah bin nida ), the opening of the number khabariyah (al istiftah bi al-sum al khabariyah), the opening of the oath (al istiftah bil qasam), the opening of the condition (al-istiftah bi syarat), opening with the command (amr bil al istiftah), opening with question (al istiftah bil istifham), opening with a prayer / sentence (Al istiftah bid Du'a), and the opening of the reason (al istiftah bit ta'lil). Of the ten kinds of opening at the top, there is educational value that can be applied in the learning process in order to achieve educational goals. Among them is a good way to open lessons, praise and reward (reward and punishmant) provided by the teacher to the students to increase interest and motivation in learning, and administration of the question as a stimulus that encourages children to think and always learning.